The ratification of ILO conventions: a failure time analysis - Bernhard Boockmann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
There are over 180 ILO conventions in many areas of labour law, industrial relations and social security, but they are not ratified universally: for the conventions adopted between 1975 and 1995, the cumulated probability of ratification is about 13 per cent ten years after their adoption. In this paper, the ratification decision is understood as a transition between two states. Using duration analysis, we identify circumstances which are favourable to this transition. For industrialised countries, the ratification of ILO conventions is shown to depend on internal political factors such as the preferences of actors from governments or trade unions. For developing countries, the only variables which are significant relate to the economic costs of ratification. There is no evidence for external pressure bearing on the ratification decision. Among industrialised member states, there is a clear downward trend in estimated ratification probabilities over the last two decades.
Keywords: D78; 330; International labour standards; ILO; international organisations; transition data; duration analysis; Internationale Sozialstandards; Abstimmung; Statistische Bestandsanalyse; Public Choice; Schätzung; Industriestaaten; Entwicklungsländer; Ratification